2007
DOI: 10.1038/nature06135
|View full text |Cite
|
Sign up to set email alerts
|

Fire and flood management of coastal swamp enabled first rice paddy cultivation in east China

Abstract: The adoption of cereal cultivation was one of the most important cultural processes in history, marking the transition from hunting and gathering by Mesolithic foragers to the food-producing economy of Neolithic farmers. In the Lower Yangtze region of China, a centre of rice domestication, the timing and system of initial rice cultivation remain unclear. Here we report detailed evidence from Kuahuqiao that reveals the precise cultural and environmental context of rice cultivation at this earliest known Neolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
245
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(257 citation statements)
references
References 22 publications
7
245
2
3
Order By: Relevance
“…Our genetic approach showed that the middle area of the Pearl River in Guangxi province, southern China, was probably the place of the first development of cultivated rice (Fig. 4b-d), although an archaeological finding had identified the Lower Yangtze region in eastern China as one of the centres of rice cultivation 14,15 . These results suggest a model in which japonica was first domesticated from Or-III in southern China, and was subsequently crossed to local wild rice in South East Asia and South Asia, thus generating indica after many cross-differentiation-selection cycles (Fig.…”
Section: Article Researchmentioning
confidence: 93%
See 2 more Smart Citations
“…Our genetic approach showed that the middle area of the Pearl River in Guangxi province, southern China, was probably the place of the first development of cultivated rice (Fig. 4b-d), although an archaeological finding had identified the Lower Yangtze region in eastern China as one of the centres of rice cultivation 14,15 . These results suggest a model in which japonica was first domesticated from Or-III in southern China, and was subsequently crossed to local wild rice in South East Asia and South Asia, thus generating indica after many cross-differentiation-selection cycles (Fig.…”
Section: Article Researchmentioning
confidence: 93%
“…Despite the fact that rice is a major cereal and a model system for plant biology, the evolutionary origins and domestication processes of cultivated rice have long been debated. The puzzles about rice domestication include: (1) where the geographic origin of cultivated rice was, (2) which types of O. rufipogon served as its direct wild progenitor, and (3) whether the two subspecies of cultivated rice, indica and japonica, are derived from a single or multiple domestications.A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the ecology in the Yangtze Delta in the Mid-Holocene improved, rice cultivation became greatly developed [13,14,21]. However, the studies of the Tianluoshan site have also confirmed that rice cultivation was affected by sea level fluctuations.…”
Section: Impacts Of Sea-level Rise On Human Dietmentioning
confidence: 99%
“…Such fluctuations in the presence of rice might have reflected issues of availability and supply on the northern edge of its range. After Jiahu and Shangshan, further archaeological evidence for the intensification of rice exploitation comes from Kuahuqiao in northern Zhejiang (ZPICRA 2004;Zong et al 2007). Dating to c.6,000 BC, this site has yielded a waterlogged canoe, wooden paddles, foundations of pile dwellings, a small proportion of morphologically domesticated rice (most grains still have wild morphologies) that resembles the japonica subspecies, and a possibility of pig domestication .…”
mentioning
confidence: 99%